The use of field data from the faulted margin of the gulf of Corinth as input to the reservoir model of the Lavrans Field, Haltenbanken, offshore Norway - SVERDRUP, E.; SKOV, T.; SOLHEIM, M.; AARSETH, E.; GABRIELSEN, R. H. (Bulletin of the Geological Society of Greece, 2001)
Large proportions of the structural features that can impact on the flow properties of a reservoir are below the resolution of seismic data. Understanding the spatial distribution and internal structure of faults is therefore fundamental. By using a field analogue from the southern margin of the Gulf of Corinth, we have obtained information about fault parameters like frequency, orientation and linkage, which have been used in the reservoir modelling process of the Lavrans Field, offshore Norway. The link between field observations, seismic interpretation and plaster modelling techniques has further guided us to describe the structural development of the investigated structures.